A framework for enhanced decision making in construction organisations based on quality of pipeline information : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy, School of Built Environment, Massey University, New Zealand - Moshood, Taofeeq Durojaye (Massey University, 2025)
The New Zealand government actively pursues the development of a sustainable construction sector that ensures high performance, productivity, innovation, and community well-being through diverse project initiatives spanning residential, non-residential, and infrastructure development. Despite these aspirations, construction projects in New Zealand are frequently delayed and not effectively completed, thus leading to underperformance. Two critical factors contributing to project delays and suboptimal outcomes are inadequate quality of information and ineffective strategic decision-making processes. Formulating effective strategic decisions is a fundamental challenge for construction organisations, significantly impacting their overall strategic goals and operational success. While information management and decision execution are widely recognised as crucial elements in organisational strategy, there remains a notable gap in understanding the intricate relationship between the quality of information and strategic decision-making, particularly within the context of construction business performance. This research addresses this critical knowledge gap by identifying the determinants for successful construction business performance. It investigates the mediating role of quality of information in the relationship between strategic decision-making and the performance of construction businesses in New Zealand. The study employs a comprehensive methodological approach combining systematic literature review, quantitative analysis, and stakeholder validation to develop a robust understanding of these complex relationships. The systematic literature review focused specifically on identifying critical determinants for successful construction business performance in New Zealand, utilising the ATLAS.ti 9 tool for analysis. This comprehensive review highlighted the fundamental role of the quality of information in strategic decision-making processes and its subsequent impact on organisational performance. This systematic analysis led to the development of a conceptual framework and associated hypotheses establishing the relationships between these factors and their impact on strategic decision-making, information quality, and construction business performance. A quantitative survey was conducted with 102 respondents, and the sample size was determined using G*Power analysis to ensure statistical validity. The study examined how strategic decision-making and information quality influence construction business performance in New Zealand. The research method that was employed integrated established theoretical models and employed Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS4 software. This analytical approach allowed for robust testing of both direct relationships between variables and the mediating effect of information quality on the relationship between strategic management practices and business performance outcomes. The findings revealed a strong positive correlation between strategic decision-making management and construction business performance, with quality of information serving as a crucial mediating factor. A key research component involved validating the proposed strategic decision-making process framework for its sufficiency, clarity, coherence, relevance, and applicability in New Zealand construction organisations. This validation process included in-depth interviews with six industry experts representing various organisational approaches to strategic decision-making. Their responses revealed a spectrum of techniques ranging from highly structured to more informal methodologies, providing valuable insights into the practical application of strategic decision-making frameworks in different organisational contexts. The research outcomes significantly contribute to theoretical understanding and practical application in the construction industry. Establishing clear criteria for successful quality of information and identifying critical factors affecting project implementation success, this study offers valuable guidance for improving practices within the construction sector. The findings emphasise the crucial importance of prioritising both the quality of information and strategic decision-making to effectively lessen project delays and optimise overall performance in the construction sector. Furthermore, the research contributes to developing more effective strategic decision-making processes by highlighting the interconnected nature of the quality of information and strategic planning. The validated framework provides construction organisations with a practical tool for enhancing their strategic decision-making capabilities while considering the critical role of quality of information in achieving successful outcomes. This study's findings have significant implications for construction industry stakeholders, such as project managers, organisational leaders, and policymakers. The research demonstrates that improving the quality of information and strategic decision-making processes can enhance project outcomes and overall organisational performance. The validated framework offers a structured approach for organisations to assess and improve their current practices while considering their unique operational contexts and requirements.
Keywords: construction management; Construction industry; New Zealand; Decision making; Information resources management; Construction projects; Planning; Data processing; 330202 Building construction management and project planning; 460209 Planning and decision making